2017
DOI: 10.1177/1534735417713301
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Personalized Exercise Recommendations During Rehabilitation on the Sustainability of Objectively Measured Physical Activity Levels, Fatigue, and Fatigue-Related Biomarkers in Patients With Breast Cancer

Abstract: Purpose. Only one-third of patients with breast cancer reach the recommended activity level of 15 to 25 MET h/wk. The aim of this study was to determine the influence of personalized exercise recommendations during rehabilitation on patients’ physical activity level, fatigue, and self-perceived cognitive function as well as on side effect–associated biomarkers. Methods. Total metabolic rate, physical activity level, mean MET and steps, fatigue, self-perceived cognitive functioning , and biomarkers (C-reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 37 publications
0
22
0
4
Order By: Relevance
“…They examined 113 randomized clinical studies with 11,525 patients. Zimmer et al [30] with a rehabilitation program including 60 patients and MenesesEchavez et al [31] with a systematic review of 14 RCTs showed that physical activity levels can increase with personalized exercise recommendations and supervised exercise interventions among breast cancer patients. The recommended training approaches and intensities are based on the level of fatigue (mild, moderate, or severe) in cancer survivors.…”
Section: Fatiguementioning
confidence: 99%
“…They examined 113 randomized clinical studies with 11,525 patients. Zimmer et al [30] with a rehabilitation program including 60 patients and MenesesEchavez et al [31] with a systematic review of 14 RCTs showed that physical activity levels can increase with personalized exercise recommendations and supervised exercise interventions among breast cancer patients. The recommended training approaches and intensities are based on the level of fatigue (mild, moderate, or severe) in cancer survivors.…”
Section: Fatiguementioning
confidence: 99%
“…Tag der Intervention. Nach einem individualisierten Trainingsprogramm, das analog zu [7] durchgeführt wurde, ergab sich eine Verbesserung in allen durch das Sense-Wear Armband erfassten Messvariablen (Gesamtumsatz, aktiver Energieumsatz, Schritte und durchschnittliche MET-Werte), 8 Monate nach der Intervention [13]. Wochen LMIE festgestellt werden [14].…”
Section: Methodikunclassified
“…Insgesamt 5 Untersuchungen mit sehr heterogenen Trainingsprogrammen konnten positive Effekte aufzeigen. Davon erfassten allerdings nur 3 den weiteren Verlauf des Aktivitätsniveaus nach der Reha [7,13,17]. Nur eine Studie setzte in der Follow-Up-Testung auf eine objektive Erfassung des Aktivitätsniveaus, verzichtete aber auf eine Kontrollgruppe [13].…”
Section: Diskussionunclassified
See 2 more Smart Citations